Prevalence of Hepatitis B e Antigen in Chronic HBV Carriers in North-central Nigeria (Journal of Health, Population and Nutrition, 2013)
Hepatitis B virus (HBV) is an important clinical problem due to its worldwide distribution and potential of adverse sequelae, including hepatocellular carcinoma (HCC). We studied the prevalence of hepatitis B virus e antigen (HBeAg) among individuals determined to be HBV surface antigen-positive (HBsAg+) and analyzed the gender/age category associated with more active HBV infection. A total of 572 HBsAg+ individuals, as determined by a double antibody sandwich ELISA method, participated in the study. They were tested for HbeAg, using a lateral flow chromatographic immunoassay. One hundred and ten individuals were found to be HBeAg-positive giving an overall prevalence of 19.2%. Of these 110 individuals, 20 (18.2%) were females, and 90 (81.8%) were males. Thus, the prevalence of HBeAg appears to be higher in males than in females (p